2017
DOI: 10.3357/amhp.4780.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Effects on Cycling During Acute Hypoxic Exposure

Abstract: Inspiratory muscle training reduced the physiological demand of moderate intensity exercise during acute hypoxic, but not normoxic, exercise. It may therefore be of benefit in adults exercising in a hypoxic environment.Lomax M, Massey HC, House JR. Inspiratory muscle training effects on cycling during acute hypoxic exposure. Aerosp Med Hum Perform. 2017; 88(6):544-549.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Similar findings of improved respiratory muscle efficiency following in RMT have been observed in hypoxia as well (40, 64). Salazar-Martinez (64) found that six weeks of pressure-threshold IMT improved ventilatory efficiency in both normobaric normoxia and normobaric hypoxia, measured by the slope of the ratio of V̇ E and V̇CO 2 (V̇ E /V̇CO 2 slope) from the beginning of exercise until the second ventilatory threshold.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar findings of improved respiratory muscle efficiency following in RMT have been observed in hypoxia as well (40, 64). Salazar-Martinez (64) found that six weeks of pressure-threshold IMT improved ventilatory efficiency in both normobaric normoxia and normobaric hypoxia, measured by the slope of the ratio of V̇ E and V̇CO 2 (V̇ E /V̇CO 2 slope) from the beginning of exercise until the second ventilatory threshold.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, although time trial performance was improved in both normoxia and hypoxia following RMT, TT performance was only correlated with OUES, and not V̇ E /V̇CO 2 slope, suggesting that, in the context of the influence of IMT on performance in hypoxia, OUES may be a better index of ventilatory efficiency than V̇ E /V̇CO 2 slope. Lomax et al (40) confirmed that ventilatory efficiency, estimated by the ratio of peripheral capillary oxygen saturation (S p O 2 ), measured by pulse oximetry, to V̇ E (S p O 2 /V̇ E ) was improved following RMT in hypoxia, but observed no differences in S p O 2 /V̇ E in normoxia following RMT. The authors speculated that an increase in lung diffusion capacity could be a potential mechanism, similar to the findings of Downey et al (14), although this hypothesis needs to be further investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All of the cross-sectional studies discussed here (see Supplementary Table 1) demonstrated that RMT could bean useful tool for improving ventilatory efficiency and delaying the onset of premature fatigue during exercise in conditions of hypoxia (Downey et al, 2007; Esposito et al, 2010; Lomax, 2010; Helfer et al, 2016; Lomax et al, 2017; Salazar-Martínez et al, 2017). Only Esposito et al (2010) were somewhat cautious with the benefits of RMT for physical performance in hypoxia.…”
Section: Resultsmentioning
confidence: 90%
“…Under these conditions, subjects are commonly advised to follow various recommendations: (1) to rest adequately, (2) to optimize nutrition and hydration, (3) iron intake and, (4) to perform only moderate physical activity. Recently, the inclusion of RMT has been proposed as a preparatory method to enhance the respiratory muscle efficiency 4–6 weeks before athletes and climbers are exposed to hypoxia/altitude (Downey et al, 2007; Esposito et al, 2010; Lomax, 2010; Helfer et al, 2016; Lomax et al, 2017; Salazar-Martínez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%